IN FAULT DETECTION AND RELIABILITY ENHANCEMENT ALGORITHM FAILURE CALCULATION METHODS - Kuchkarova, Dilnoza Toptiyevna (Educational Research in Universal Sciences, 2023)
The development and forecasting of electric motor maintenance requirements is related to a model-based fault detection system and method. Since the method and system of the model are based on software and use the information obtained as a result of uncertain measurements, the implementation phase requires much less cost than the previous maintenance methods.